Short Takes: The Canadian Worker on Film - Frank, David (Labour/Le Travailleur, 2000)
Abstract Is there a Canadian labour film? After a century of film production in Canada, the answer is uncertain. Canadian workers do appear in a variety of documentary and feature film productions, but their presence often arises from the incidental processes of documentation and fictionalization. There is also a more purposeful body of work focused on the concerns of labour history, but its promise remains relatively underdeveloped. Although film has become one of the dominant languages of communications at the end of the 20th century, the practice of visual history stands to benefit from closer collaboration between historians and film-makers.